Students’ identification with academic athletic associations and its effect on student engagement with higher education institutions (Educação e Pesquisa, 2022)
There are more than 2 thousand higher education institutions (HEIs) in Brazil, housing around 8 million students, of which a significant portion are involved in extracurricular activities – such as sports through Academic Athletic Associations (AAAs). These associations tend to offer a series of benefits, including a strengthening of students’ ties with the institution, contributing to their permanence in it. Considering the importance of understanding more about athletic associations, the main goal of this research was to analyze the antecedent and consequent variables of students’ identification with them, and the secondary goal was to discuss how students’ identification with athletic associations may contribute to student engagement with the HEI. The theoretical framework supporting the hypotheses proposed included identification theory, the athletic associations inside HEIs, and antecedent and consequent variables of student identification with AAAs. This is a descriptive study with a sample of 506 AAA members in several HEIs in Brazil. The model proposed was tested via Structural Equation Modeling. The findings showed that, among the constructs taken into consideration, only connection with the AAA brand was an antecedent variable of identification with the association, accounting for 72.4% of the variance in identification. The findings showed that the remaining eight constructs are consequent variables of identification with AAAs. In addition, it was possible to infer that students’ identification with AAAs may contribute to student engagement with the educational institution.